The development of written word processing: the case of deaf children - Leybaert, Jacqueline (1989)
Reading is a highly complex, flexible and sophisticated cognitive activity, and word recognition constitutes only a small and limited part of the whole process. It seems however that for various reasons, word recognition is worth studying separately from other components. Considering that writing systems are secondary codes representing the language, word recognition mechanisms may appear as an interface between printed material and general language capabilities, and thus, specific difficulties in reading and spelling acquisition should be iodated at the level of isolated word identification (see e. g. Crowder, 1982 for discussion). Moreover, it appears that a prominent characteristic of poor readers is their lack of efficiency in the processing of isolated words (Mitche11,1982; Stanovich, 1982). And finally, word recognition seems to be a more automatic and less controlled component of the whole reading process.